Distinct Cutibacterium acnes subspecies defendens strains classified by multi-omics dissection alleviate inflammatory skin lesions of a rosacea-like mouse model - Kim, Hanseol; Lee, Kihyun; Lee, Ji Young; Kwon, Bo Eun; Kim, Hyun Jeong; Park, Hyunkyung; Kim, Taekyung; Kwak, Jun-Gu; Choi, Joung Eun; Hong, Kwang Hee; Chun, Jongsik; Shin, Changsik (Frontiers in Microbiomes, 2024)
IntroductionCutibacterium acnes (C. acnes) resides in various organs such as the skin, prostate, eye, nose, stomach, and intestine, indicating the possibility of extensive crosstalk between this bacterium and the human body. C. acnes strains are classified into three subspecies based on phylogenetics and distinguishable phenotypes. Among them, C. acnes subsp. defendens strains are characterized by anti-inflammatory features, raising expectations for their potential as future microbiome therapeutics. However, the heterogeneity of C. acnes subsp. defendens and its corresponding immunological functions have not been clearly addressed.MethodsThe genetic diversity of the strains was assessed using single- and multi-locus sequence typing. Their immune-modulatory functions were evaluated in vitro using 2D and 3D assays with immune and epithelial cells. The anti-inflammatory effects were further confirmed in vivo using a rosacea-like mouse model. Comparative genomic and transcriptomic analyses were conducted to uncover mechanisms underlying the immunosuppressive activity of the strains.ResultsWe demonstrated that the newly isolated C. acnes subsp. defendens strains, exhibiting phenotypic heterogeneity, are distinctly clustered using single- and multi-locus sequence typing methods. These strains showed strong immune-regulatory functions in immune and epithelial cell-based 2D and 3D in vitro assays. Furthermore, their anti-inflammatory role was functionally confirmed in vivo using a rosacea-like mouse model, where they alleviated skin lesions characterized by hyperplasia and dermal inflammation. Comparative transcriptomics revealed that these strains may exert their immunosuppressive effects through the enhanced expression of acnecins and transcriptional variation in envelope stress regulators (specifically the two-component systems, CesSR homologs). Additionally, we propose that these C. acnes type II strains produce anti-inflammatory metabolites or peptides smaller than 3 kDa, which are associated with elevated pyrimidine and reduced L-arginine biosynthesis.DiscussionThe newly isolated C. acnes subsp. defendens strains demonstrate significant anti-inflammatory properties both in vitro and in vivo, suggesting their potential as microbiome-based therapeutics. Their unique genomic and transcriptomic profiles, including the production of small bioactive compounds and specific transcriptomic patterns, underpin their immunosuppressive capabilities. These findings provide a foundation for developing novel treatments for inflammatory skin conditions, such as rosacea.